2002
DOI: 10.3168/jds.s0022-0302(02)74191-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Time on Nitrogen Capture by Lactating Dairy Cows Grazing Rye Pasture

Abstract: The objective of this experiment was to determine whether varying times at which a partial mixed ration was fed, either before or after grazing, affected N utilization from rye pasture and thus affected milk yield and components. Sixteen Holstein cows were fed a partial mixed ration (PMR) either at 0700, 0830, or 1100 h. Cows were milked at 0900 h and turned out to graze at 0930 h. Treatments represented feeding times 2.5 h and 1 h before grazing and immediately after grazing. The study was conducted as a 3 x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Some studies have improved nitrogen utilization efficiency in grazing dairy cows by altering the timing of concentrate supplementation (Vaughan et al . ; Trevaskis et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have improved nitrogen utilization efficiency in grazing dairy cows by altering the timing of concentrate supplementation (Vaughan et al . ; Trevaskis et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a period without access to feed before grazing will increase the rate of intake (Patterson et al, 1998). However, this effect is primarily observed immediately after start of the pasture period, and diminishes over the day (Patterson et al, 1998;Vaughan et al, 2002). Hernandez-Mendo and Leaver (2004) found that the intake rate during grazing decreased both with shorter and longer time at pasture compared with 10 h in a system with a combination of indoor ad libitum feeding and grazing for a restricted period.…”
Section: Introductionmentioning
confidence: 99%
“…Altering time of concentrate supplementation has been shown to improve nitrogen utilization efficiency in grazing dairy cows by synchronizing easily fermentable carbohydrate supply to herbage protein degradation in the rumen (Vaughan et al . ; Trevaskis et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown improved nitrogen utilization efficiency in grazing dairy cows by altering the time of carbohydrate supplementation (Vaughan et al . ; Trevaskis et al . ; Mitani et al .…”
Section: Introductionmentioning
confidence: 99%